Ceramics utilizing glass fiber-reinforced plastic as civil engineering materials to counteract the heat island phenomenon - Yusuke YASUDA (The Japan Society of Mechanical Engineers, 2016)
This study is aimed at the development of civil engineering materials such as pavement blocks and building tiles that can moderate the heat island phenomenon. This is achieved by exploiting properties such as the material porous structure, high water absorption capacity and high strength of ceramics produced by mixing clay and crushed waste glass fiber-reinforced plastic (GFRP) before firing. Fundamental properties, such as pore size distribution, water absorption capacity, solution pH after ceramic immersion, bending strength, freezing resistance performance and thermal conductivity of ceramic specimens with varying ratios of clay and GFRP were clarified. The radiant heat reduction performance of the ceramic was examined by measuring the surface temperatures of a ceramic sample made from clay, a ceramic sample made by mixing 20% GFRP with clay, and a mortar sample in water-saturated and dry states while their surfaces were irradiated with infrared light. To clarify the difference in temperature-reducing ability by evaporation heat on each sample, the amount of water evaporated from a sample that had absorbed water and was irradiated with infrared light was measured. The rate of heat-absorption from the sample by water evaporation was estimated. The temperature-reducing effect by evaporation heat of the sample during water-absorption was verified quantitatively by thermal conductivity analysis using finite element methods. While water-saturated, a 20% GFRP/clay ceramic sample could reduce the increase in temperature caused by radiant heat considerably, and for an extended duration. It is expected that such ceramics could be used in civil engineering materials to counteract the heat island phenomenon.